2011
DOI: 10.1089/zeb.2011.0704
|View full text |Cite
|
Sign up to set email alerts
|

Production of F1Offspring with Vitrified Sperm from a Live-Bearing Fish, the Green SwordtailXiphophorus hellerii

Abstract: This study reports the first production of offspring with vitrified sperm from a live-bearing fish Xiphophorus hellerii. The overall goal of this study was to develop streamlined protocols for integration into a standardized approach for vitrification of aquatic species germplasm. The objectives were to (1) estimate acute toxicity of cryoprotectants, (2) evaluate vitrification solutions, (3) compare different thawing methods, (4) evaluate membrane integrity of post-thaw sperm vitrified in different cryoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Crispe [10] found that only 82 % of the human monocytes still appeared viable after incubation at 3 × 10 −1 M of MPD. Nacci et al [11] determined that MPD had exceptionally toxic effect to sperm which had also been confirmed by Cuevas-Uribe et al [8]. Procter [12] reported that MPD could depress the central nervous system and had a toxic action on the kidneys as well as the liver.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Crispe [10] found that only 82 % of the human monocytes still appeared viable after incubation at 3 × 10 −1 M of MPD. Nacci et al [11] determined that MPD had exceptionally toxic effect to sperm which had also been confirmed by Cuevas-Uribe et al [8]. Procter [12] reported that MPD could depress the central nervous system and had a toxic action on the kidneys as well as the liver.…”
Section: Introductionmentioning
confidence: 76%
“…Because of those special properties, MPD has become a very important compound. MPD is widely used as a chemical intermediate [2], a solvent for perfume and cosmetics [3,4], an excipient in the formulation [5], an organic additive to promote the phase transition [6], antibacterial and antifungal agent [7], a cryoprotectant [8] and a single most successful agent promoting crystallization of biological macromolecules [1], and so on [9]. MPD is regarded as a high volume chemical (HVC) with production exceeding 0.5 × 10 6 kg annually in the United States [3].…”
Section: Introductionmentioning
confidence: 99%
“…Small fishes include ornamental aquarium species and important biomedical models Medaka ( Oryzias latipes ), Xiphophorus spp., and Zebrafish ( Danio rerio ) (Yang and Tiersch 2009). Small fishes are also disproportionately observed on lists of imperiled species and are in need of germplasm repositories for conservation (Cuevas-Uribe et al 2011a; Cuevas-Uribe et al 2011b). In addition, vitrification does not require specialized equipment and can be done in remote locations such as in the field where endangered fishes occur in the wild.…”
mentioning
confidence: 99%
“…First is the lack of devices specifically designed for use with aquatic species, forcing researchers to experiment with devices designed for other uses such as vitrification of human embryos (Kása et al 2016). Other options are to use devices not designed for vitrification, such as microbiology inoculation loops (Cuevas-Uribe et al 2011b; Kuwayama 2007). In addition, there are a large number of technical variables that are not standardized in this research, making it problematic or impossible to directly compare vitrification results among studies.…”
mentioning
confidence: 99%
“…Such devices are intrinsic to cryobiology research, but pose the inherent problems of dealing with cryogenic temperatures [3]. As such, these devices are often expensive and designed for highly specialized purposes (such as freezing of human embryos [6]) which reduce their utility for adaptation for other applications (such as vitrification of fish sperm [2]). The paucity of existing devices also constrains the starting points for development of new devices, and accordingly cryobiological devices often have to be crafted from simple or readily available materials such as French straws [11].…”
mentioning
confidence: 99%